Datopotamab deruxtecan in breast cancer treatment: a systematic review of clinical efficacy and safety - Julia Piekarz; Natalia Picheta; Jakub Pobideł; Natalia Gierulska; Krzysztof Kułak; Rafał Tarkowski (Frontiers in Immunology, 2026)
Background Breast cancer (BC) remains the most common malignant tumor in women worldwide and a leading cause of cancer-related deaths. Despite therapeutic advances, patients with advanced BC, particularly triple-negative breast cancer (TNBC), still face limited effective treatment options. Antibody-drug conjugates (ADCs) represent a compelling strategy that combines precise tumor targeting with cytotoxic payloads, effectively bridging targeted delivery with microenvironmental disruption. Datopotamab deruxtecan (Dato-DXd), a Trop-2-targeted ADC, has demonstrated encouraging clinical activity. Preclinical evidence suggests that Dato-DXd may modulate the tumor microenvironment (TME) through potential induction of immunogenic cell death (ICD), providing a biological rationale for investigating synergistic combinations with immunotherapy. Materials and methods A systematic review was conducted in accordance with PRISMA guidelines using the PubMed, Web of Science, and ClinicalTrials databases. The inclusion criteria targeted relevant clinical studies published between 2024 and 2026. Ultimately, after a thorough analysis, one randomized controlled trial (RCT) and one single-arm study met the eligibility criteria and were included in the review. Results Data analysis from the Phase III TROPION-Breast01 trial demonstrated that Dato-DXd significantly improved objective response rate (ORR) and median progression-free survival (PFS) compared to investigator’s choice chemotherapy in patients with HR+/HER2- breast cancer. In the Phase I TROPION-PanTumor01 trial, Dato-DXd showed promising clinical activity in both HR+/HER2- breast cancer and TNBC cohorts. Regarding safety, Dato-DXd was associated with a lower incidence of grade ≥ 3 adverse events compared to standard chemotherapy in the randomized setting, although low-grade toxicities such as stomatitis and nausea remained common. Conclusion Dato-DXd demonstrates robust clinical activity in patients with BC, providing superior disease control with a favorable safety profile compared to conventional chemotherapy. Beyond direct tumor cell ablation, its mechanism of action includes a potent bystander killing effect, while preclinical data suggest that the induction of ICD may contribute to reshaping a heterogeneous TME. Future research is needed to correlate these preclinical mechanistic hypotheses with clinical outcomes. The limited number of available RCTs and Real-World Evidence (RWE) studies underscores the need to raise awareness and conduct further research to identify predictive biomarkers and evaluate combinations with immune checkpoint inhibitors to optimize personalized treatment regimens. Systematic review registration https://www.crd.york.ac.uk/prospero/ , identifier CRD420261408796.